Abrogation by Trifolium alexandrinum root extract on hepatotoxicity induced by acetaminophen in rats. (January 2014) - Sakeran, Mohamed I.; Zidan, Nahla; Rehman, Hasibur; Aziz, Al Thbiani; Saggu, Shalini
<x content-type="archive" xml:space="preserve">Abstract</x> Objective Acetaminophen (APAP) is a substance that harms human health by stimulating free radical production. This study investigated the ability of Trifolium alexandrinum root (TAR) extract to reduce the hepatotoxicity induced by APAP in rats. Methods Animals were classified into four groups and treated for 6 weeks. Group 1: normal control-treated (saline); Group 2: TAR extract-treated (100 mg/kg); Group 3: APAP-treated; Group 4: APAP plus TAR extract. Results APAP significantly elevated AST (aspartate amino transferase), ALT (amino alanine transferase), ALP (alkaline phosphatase), GGTP (gamma glutamyl transpeptidase), bilirubin, and malondialdehyde with a significant decrease in glutathione, superoxide dismutase, glutathione peroxidase, catalase, and glutathione S-transferase compared with the control group. Administration of TAR extract combined with APAP improved the liver damage induced by APAP. Histopathological evidence, together with observed DNA fragmentation, supported the detrimental effect of APAP and the ameliorating effect of TAR extract on liver toxicity. Conclusion TAR extract has beneficial properties and can reduce the liver damage and toxicity induced by APAP. Discussion Free radical mediated processes have been implicated in the pathogenesis of many diseases. The protective effect of TAR root extract on APAP-induced hepatotoxicity in rats appears to be related to inhibition of lipid peroxidation and enhancement of antioxidant enzyme levels, in addition to a free radical scavenging action.